Increasing biological N2 fixation and its contribution to the N cycle in alley cropping - Sanginga, N.; Mulongoy , K. (1995)
Biological N2 fixation (BNF) of hedgerow trees, organic mailer decomposition and nutrient transfer to associated food Crops are the major processes which should actualize the expected benefits of alley cropping systems. Leucaena leucocephala or Gliricid,a sepium can fix between 134 and 274 kg N2 ha-1 yr-1 under field conditions. There are large genotypic and microbial symbiont differences between varieties of a single tree species resulting in different N2 fixation, and differences in tolerance 10 soil constraints such as low P and high acidity. Management practices such as pruning regimes affect N2 fixation and its contribution to the N cycle. Nodule senescence and decay occurred within 3 weeks after pruning, and new nodules are being formed 10 continue N, fixation during regrowth. Approximately half of the fixed N2 is found in below ground plant parts. Large quantities of N are harvested with hedgerow prunings (>300 kg N ha-1 yr-1) but N contribution to crops is in the range of 40-70 kg N ha" per season. This represents about 20-30% of N applied as prunings. Below ground, trees are estimated to transfer by root turnover and nodule decay an estimated 25 kg N ha-1 to soil. Low N use efficiency by crop due to lack of synchronization between crop N demand and the N supply of prunings has been examined.